IoT Enabled Low-Cost Indoor Air Quality Monitoring System - Kaur, Supreet (My University, 2019)
Internet of Things (IoT) is considered as revolution in technology sector. It has ability to automate mundane tasks and simplify lives of people. IBM define IoT as “It is the concept of connecting any device to the internet and other connected devices”. IoT can be seen in all areas of life such as homes, industries, healthcare, transport, environment monitoring etc. The present work has been done on one such application of IoT, i.e. Indoor Air Pollution Monitoring. Today, air is the most polluted resource around the globe. It is the essential element required for living and needs immediate attention of people from all professions. Even, indoor air is not safe. In fact, it is more polluted than outdoor air. In this research, the prototype of indoor air quality monitoring device has been built. The two most dangerous and common indoor air pollutants have been addressed i.e. carbon dioxide (CO2) and particulate matter (PM). Low-cost semiconductor sensors have been used for calculating above mentioned pollutant concentrations. An android application has been built for users to see their indoor air quality. The result shows poor air quality caused by different household and workplace activities and provides plant based solutions for controlling indoor air pollution.
Keywords: Indoor Air Quality Monitoring System(IAQMS); Indoor Air Pollution; Pollutant Classification; IoT; Wireless Sensor Network